PENGARUH IKLAN MIZONE 3D PADA MEDIA LUAR RUANG TERHADAP BRAND IMAGE - Santoso, Prasetya Yoga (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The effectiveness of the use of billboards (billboards) of an advertising campaign is determined by various factors other than the determination of the location. The following points are worth noting, namely range, continuity, size and color. Therefore, to be able to carry out effective promotional activities in order to create a brand image on brand products, the manufacturers need to explore further the factors that influence the creation of these things. Based on this, the study aims to determine the 3D Mizone advertising on outdoor media (billboards), to determine the brand image Perbanas Students of the Faculty of Economics at the Institute and to find out how much the relationship Mizone 3D advertising on outdoor media (billboards) with the brand image students of the Faculty of Economics and Business in Perbanas Institute as well as to determine how much influence ads Mizone 3D on outdoor media (billboards) to the brand image of students of the Faculty of Economics at the Institute Perbanas. The method used is an explanatory nature. The research object was a student at the Faculty of Economics and Business in Perbanas Institute, which amounts to 78 people. âre Making sampling technique using simple random sampling. Techniques of data collection is done by distributing questionnaires to the respondents technique and literature from the existing literature. The result is that the respondentsâ assessment of the faculty of economics and business students in Perbanas Institute on 3D Mizone brand image advertising on outdoor media (billboards) obtained a total score of 3307 categories included in the category of respondents agreed, meaning that the use of 3D advertising on brand image Mizone student faculty of economics and business suit and has got a good assessment.